Subsurface effects in the dissociation of H-2 on Pd(111) - Munn, N; Clary, D (1997)
Using a time-independent quantum mechanical method based on hyperspherical coordinates and a reduced-dimensionality approximation, we carry out a study of H2 dissociation to subsurface states of Pd(111). Particular attention is paid to the effect of rotation on the dissociation probability, and the existence of 'mixed' states spanning surface and subsurface is discussed.